TAFSIR JALÂL AL-DÎN AL-SUYÛTÎ & IBN JARÎR AL-TABARÎ PADA AL-MÂIDAH: 51 (Studi Tafsir Muqâran) - komarudin komarudin (Ibn Abbas : Jurnal Ilmu Alquran dan Tafsir, 2022)
Abstract  This article aims to reveal the interpretation of Jalaladdîn al-Suyûtî and Ibn Jarîr al-Tabarî about making Jews and Christians as leaders through their interpretation of the Qur'an in Surah al-Mâidah verse 51 and introduce the interpretation of muqāran. In fact, much literacy regarding to interpretations of al-Maidah verse 51 have been found, but among these literacy do not show the main source so that it feels far from substance. Helmy Zakaria for example, he wrote “VARIETY OF NETIZEN'SINTERPRETATIONS    ABOUT    NON-MUSLIM    LEADERS;    Study    on    theInterpretation of Surah al-Maidah verse 51 " This article is packaged using a qualitative method which is began by dissecting the works of al-Suyûtî and al-Tabarî; al-Dârr al-Mantsûr fî Tafsr al-Mantsûr and Jâmi' al-bayân fî Tawîl al-Qurân. Then it is compared, analyzed, and conluded. This article concludes that Ibn Jarîr al-Tabarî and Jalâluddîn al-Suyûtî condemned the prohibition of making Jews and Christians as guardians/meeting friends/leaders on the grounds of following qâ'idah al-Ashl fi al-Nahy li al-Tahrim  Keywords: al-Mâidah, al-Suyûtî, al-Tabarî, Leader, Jews, Christians